Molecular Distance to Health Transcriptional Score and Disease Severity in Children Hospitalized With Community-Acquired Pneumonia - Wallihan, Rebecca G.; Suárez, Nicolás M.; Cohen, Daniel M.; Marcon, Mario; Moore-Clingenpeel, Melissa; Mejias, Asuncion; Ramilo, Octavio (Frontiers in Cellular and Infection Microbiology, 2018)
Background: Community-acquired pneumonia (CAP) is a leading cause of hospitalization and mortality in children. Diagnosis remains challenging and there are no reliable tools to objectively risk stratify patients or predict clinical outcomes. Molecular distance to health (MDTH) is a genomic score that measures the global perturbation of the transcriptional profile and may help classify patients by disease severity. We evaluated the value of MDTH to assess disease severity in children hospitalized with CAP. Methods: Children hospitalized with CAP and matched healthy controls were enrolled in a prospective observational study. Blood samples were obtained for transcriptome analyses within 24 hours of hospitalization. MDTH scores were calculated to assess disease severity and correlated with laboratory markers, such as white blood cell count, c-reactive protein (CRP), and procalcitonin (PCT), and clinical outcomes, including duration of fever and duration of hospitalization (LOS). Univariate and multivariable logistic regression were applied to assess factors associated with LOS and duration of fever after hospitalization. Results: Among children hospitalized with CAP (n=152), pyogenic bacteria (PB) were detected in 16 (11%), Mycoplasma pneumoniae was detected in 41 (28%), respiratory viruses (RV) alone were detected in 78 (51%), and no pathogen was detected in 17 (11%) children. Statistical group comparisons identified 6,726 genes differentially expressed in patients with CAP versus healthy controls (n=39). Children with confirmed PB had higher MDTH scores than those with RV (p<0.05) or M. pneumoniae (p<0.01) detected alone. CRP (r=0.39, p<0.0001), PCT (r=0.39, p<0.0001), and MDTHs (r=0.24, p<0.01) correlated with duration of fever, while only MDTHs correlated with LOS (r=0.33, p<0.0001). Unadjusted analyses showed that both higher CRP and MDTHs were associated with longer LOS (OR 1.04 [1-1.07] and 1.12 [1.04-1.20], respectively), however, only MDTH remained significant when adjusting for other covariates (aOR 1.11 [1.01-1.22]). Conclusions: In children hospitalized with CAP MDTH score measured within 24 hours of admission was independently associated with longer duration of hospitalization, regardless of the pathogen detected. This suggests that transcriptional biomarkers may represent a promising approach to assess disease severity in children with CAP.